Research on glacier DEM extraction method based on ASTER Data. Issue 1 (June 2021) - Zhang, Yashuang; Wu, Haiman; Liu, Deli
Abstract: The greenhouse effect has led to a large area shrinkage of glaciers in the west of China, resulting in great changes in glacial landforms. In this paper, we use remote sensing satellite to obtain timely and accurate DEM, and use remote sensing technology to process DEM effectively, so as to obtain high-precision results, which can be used as the basic model to study glacier area change. In this paper, the DEM of Malan ice cap in Xinqingfeng is extracted from the orthoengine module of PCI, and the results of DEM obtained are compared with the reference DEM by using aster stereo image pair, and the results of Aster meeting the accuracy requirements are analyzed, which is helpful for the application of Aster stereo image pair in DEM production process.